Locus-specific ancestry to detect recent response to selection in admixed Swiss Fleckvieh cattle - Khayatzadeh, N.; Mészáros, G.; Utsunomiya, Y. T. [UNESP]; Garcia, J. F. [UNESP]; Schnyder, U.; Gredler, B.; Curik, I.; Sölkner, J. (Wiley, 2016)
Identification of selection signatures is one of the current endeavors of evolutionary genetics. Admixed populations may be used to infer post-admixture selection. We calculated local ancestry for Swiss Fleckvieh, a composite of Simmental (SI) and Red Holstein Friesian (RHF), to infer such signals. Illumina Bovine SNP50 BeadChip data for 300 admixed, 88 SI and 97 RHF bulls were used. The average RHF ancestry across the whole genome was 0.70. To identify regions with high deviation from average, we considered two significance thresholds, based on a permutation test and extreme deviation from normal distribution. Regions on chromosomes 13 (46.3–47.3 Mb) and 18 (18.7–25.9 Mb) passed both thresholds in the direction of increased SI. Extended haplotype homozygosity within (iHS) and between (Rsb) populations was calculated to explore additional patterns of pre- and post-admixture selection signals. The Rsb score of admixed and SI was significant in a wide region of chromosome 18 (6.6–24.6 Mb) overlapped with one area of strong local ancestry deviation. FTO, with pleiotropic effect on milk and fertility, NOD2 on dairy and NKD1 and SALL1 on fertility traits are located there. Genetic differentiation of RHF and SI (Fst), an alternative indicator of pre-admixture selection in pure populations, was calculated. No considerable overlap of peaks of local ancestry deviations and Fst was observed. We found two regions with significant signatures of post-admixture selection in this very young composite, applying comparatively stringent significance thresholds. The signals cover relatively large genomic areas and did not allow pinpointing of the gene(s) responsible for the apparent shift in ancestry proportions.
Keywords: admixture; extended haplotype homozygosity; F st; iHS; local ancestry deviation; permutation; Rsb; selection signature; SNP; Swiss Fleckvieh